Combined inhibition of BET bromodomain and mTORC1/2 provides therapeutic advantage for rhabdomyosarcoma by switching cell death mechanism. Issue 8 (26th April 2022) - Srivastava, Ritesh K.; Guroji, Purushotham; Jin, Lin; Mukhtar, M. Shahid; Athar, Mohammad
Abstract: Aberrant activation of multiple complex signaling pathways underlies the pathogenesis of rhabdomyosarcoma (RMS), which remains a cause of mortality in approximately 30% of children with RMS. Bromodomain and extraterminal (BET) domain chromatin remodeling regulates several of these pathways. Here, we targeted bromodomain 4 (BRD4) in combination with another molecular metabolic tumor driver, the Akt/mTOR signaling pathway, to provide a highly effective treatment for this neoplasm. We demonstrated that a nexus of these two molecular pathways underlies RMS pathogenesis. Our data show that the combined inhibition of the BET bromodomain and mTORC1/2 signaling abrogates aggressive RMS growth. Thus, the bromodomain inhibitor RVX‐208 significantly augmented the therapeutic effects of the dual mTORC1/2 inhibitors, OSI‐027 and PP242, both in vitro and in a human xenograft murine model. Drug‐treated residual tumors showed a decrease in the activation of underlying signaling mechanisms characterized by a reduction in the expression of p‐AKT, p‐mTOR, p‐p70S6K, cyclin D1, and proliferation. Our ChIP‐seq data demonstrated that RVX‐208 effectively blocked BRD4 occupancy on its target promoters. ChIP‐qPCR assays further confirmed that RVX‐208 treatment resulted in a significant decrease in H3K27ac and H4K8ac signals at their target loci. While single RVX‐208 treatment induces apoptosis and a single mTORC1/2 inhibitor induces macropinocytosis, their combined treatment led to necroptosis‐mediated cell death. These data suggest that combined treatment with drugs targeting BRD4 and mTORC1/2 may be an effective therapeutic intervention for drug‐resistant RMS.